Pengaruh Penggunaan Gawai Terhadap Perkembangan Bahasa Anak - Dhini Kusuma Lestari; Nova Lisa Aisyah; Muhammad Irfan (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
Advances in information and communication technology, including the use of gadgets, have affected various aspects of life, including language development in early childhood. This study aims to analyze the effect of gadget use on children's language development, especially early childhood who experience speech delays. The research method used is qualitative with a descriptive approach, using in-depth interviews with parents and children as a data collection technique. The results showed that excessive use of gadgets without supervision can inhibit children's verbal interaction, reduce stimulation from the social environment, and have an impact on speech delay. Other factors, such as lack of direct interaction with parents and excessive sugar consumption, also worsen children's language development. However, with learning strategies based on direct interaction and controlled utilization of devices as learning media, children's language development can be improved. This study emphasizes the importance of parents' role in providing assistance and limiting the use of devices. The results of this study provide insights for parents, educators, and researchers to better understand the impact of technology on children's development and the importance of appropriate stimulation in supporting children's language skills.